Syngas Production from Catalytic CO2 Reforming of CH4 over CaFe2O4 Supported Ni and Co Catalysts: Full Factorial Design Screening - M. Anwar Hossain; Bamidele Victor Ayodele; Chin Kui Cheng; Maksudur R Khan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
In this study, the potential of dry reforming reaction over CaFe2O4 supported Ni and Co catalysts were investigated. The Co/CaFe2O4 and Ni/CaFe2O4 catalysts were synthesized using wet impregnation method by varying the metal loading from 5-15 %. The synthesized catalysts were tested in methane dry reforming reaction at atmospheric pressure and reaction temperature ranged 700-800 oC. The catalytic performance of the catalysts based on the initial screening is ranked as 5%Co/CaFe2O4 < 10%Co/CaFe2O4 < 5%Ni/CaFe2O4 < 10%Ni/CaFe2O4 according to their performance. The Ni/CaFe2O4 catalyst was selected for further investigation using full factorial design of experiment. The interaction effects of three factors namely metal loading (5-15 %), feed ratio (0.4-1.0), and reaction temperature (700-800 oC) were evaluated on the catalytic activity in terms of CH4 and CO2 conversion as well as H2 and CO yield. The interaction between the factors showed significant effects on the catalyst performance at metal loading, feed ratio and reaction temperature of 15 %, 1.0, and 800 oC. respectively. The 15 wt% Ni/CaFe2O4 was subsequently characterized by Thermogravimetric (TGA), X-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray Spectroscopy (EDX), X-ray Photoelectron Spectroscopy (XPS), N2-physisorption, Temperature Programmed Desorption (TPD)-NH3, TPD-CO2, and Fourier Transform Infra Red (FTIR) to ascertain its physiochemical properties. This study demonstrated that the CaFe2O4 supported Ni catalyst has a good potential to be used for syngas production via methane dry reforming.